Examining the Roots of Homelessness - The Impact of Regional Housing Market Conditions and the Social Environment on Homelessness in Germany - Alexandra Kröll; Oliver Farhauer (European Regional Science Association (ERSA), 2012)
Despite large-scale governmental efforts to combat homelessness, homelessness rates can only be reduced but not eliminated completely by the measures usually applied. Hence, there is an obvious need to investigate additional factors which contribute to homelessness and gain insights on how to further reduce homelessness. To begin with, the relationship between the conditions prevailing on the housing market and homelessness levels is made out with the help of a theoretical model. From this model, a critical income ensuring positive housing consumption can be deduced; individuals with an income below this critical threshold end up homeless. The empirical analysis draws on a panel data set comprising information on all districts (Kreise) of North Rhine-Westphalia from 2004-2009. The regression analysis underpins the theoretical results: High (net supply) rents as well as low vacancy rates among small flats lead to rising homelessness. Homelessness also increases when the share of long-term unemployed and of those with a monthly income below exteuro 700 is higher, since this makes it more difficult to reach the critical income needed to rent a flat. Finally, some policy conclusions resulting from the analysis are pointed out.
Keywords: 330